A Systematic Review of Cultural Values in Indonesian Folklore: Preserving Local Wisdom through Educational Integration - Sawita, Nada; Nazurty, Nazurty; Sulistiyo, Urip (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This systematic review examines the integration of cultural values from Indonesian folklore into educational practices, with a particular focus on the Merdeka Curriculum. The study aimed to analyze peer-reviewed articles published between 2019 and 2024 to assess the impact of folklore-based education on student learning, cultural awareness, and moral development. The research followed PRISMA guidelines, initially identifying 150 relevant articles. After applying strict inclusion and exclusion criteria, 50 articles were further analyzed, leading to the selection of 7 studies for in-depth review. The results reveal that incorporating folklore into the curriculum significantly enhances students' cultural identity, moral reasoning, and engagement in learning. However, challenges such as the adaptation of traditional folklore to modern educational contexts and the effective use of digital platforms were identified. The novelty of this study lies in its comprehensive synthesis of recent empirical evidence on the educational use of Indonesian folklore, providing insights into the potential of folklore-based education to preserve local wisdom. This review contributes to the broader discourse on cultural preservation and educational innovation, highlighting the importance of integrating indigenous knowledge into formal education to foster a culturally responsive learning environment.